Stancu modified operators revisited - Agratini, Octavian (Rev. Anal. Numér. Théor. Approx., 2002)
In this paper we construct a general positive approximation process representing an integral form in Kantorovich sense of the Stancu operators. By using K-functionals and some moduli of smoothness we give direct theorems for pointwise approximation. Also, by using the contraction principle we reobtain the convergence of the iterates of Stancu polynomials.